A Facile Method for the Synthesis of a MoS2/g‐C3N4 Photocatalyst. Issue 12 (11th September 2019) - Truong, Duy Huong; Vo, Vien; Van Gerven, Tom; Leblebici, Mumin Enis
Abstract: A MoS2 /g‐C3 N4 composite was synthesized by a significantly simple method using Na2 MoO4 and thiourea as precursors, without the need for a hydrothermal or an ultrasound step. The photocatalytic activity of the synthesized material was evaluated by the degradation of rhodamine B (RhB) in aqueous solution under blue light. The composites with low content of MoS2 performed better than pure g‐C3 N4 . Using a low‐power light‐emitting diode light source, an improvement of two orders of magnitude in the photochemical space‐time yield was achieved, proving enhanced energy efficiency and productivity compared to earlier studies. The degradation pathway of organic pollutants was confirmed by the effects of selective scavengers. Abstract : A quick and low‐cost method for the synthesis of MoS2 /g‐C3 N4 composites with thiourea and sodium molybdate as precursors is introduced. Using only two calcination steps and without any other high‐pressure or ultrasonic processes, a highly effective visible‐range photocatalyst is produced. Under optimal conditions, the reaction system exhibits high energy efficiency and productivity.